Needs Assessment for Capacity Building in Developing Routine Work into Research Among Staff of the Innovative Learning Institute, University of Phayao - Nonthamand, Narin (Journal of Graduate Research, 2025)
This research aimed to 1. assess the needs for enhancing the capacity to transform routine work into research among staff of the Innovative Learning Institute, University of Phayao, 2. evaluate the knowledge of the staff regarding the development of routine work into research, and 3. investigate the problems and obstacles in developing routine work into research among the staff. The sample group comprised 43 Innovative Learning Institute staff members at the University of Phayao. Data were collected using a needs assessment questionnaire and a knowledge test on developing routine work into research. The needs assessment was analyzed using the Modified Priority Needs Index (PNImodified) technique. Descriptive statistics, including frequency and percentage, were used to evaluate knowledge, and open-ended responses regarding problems and obstacles were analyzed using content analysis. The research findings revealed: 1. The staff had the highest required need to learn about selecting appropriate research statistics for the study topic. 2. The topic most frequently answered correctly was population and sample determination, while the least frequently answered correctly was writing the introduction and determining the validity and reliability of the research instrument. 3. The most significant problem and obstacle for staff in developing routine work into research was time constraints. These findings can serve as a guideline for developing capacity in routine-to-research initiatives, ensuring alignment with the actual needs of the staff.